Building a Prediction Model to Predict the Breast Cancer using ANNâ€™S Kernel Based Method - G, Naganandini.; R H, Vishwanth. (International Journal of Engineering and Technology, 2018)
The most vulnerable disease is Breast Cancer. Many differentÂ methods and processes were identified for the early detection and for the remedyÂ of Breast Cancer .Till date only two genes have been identified and which accounts for genetic characteristics to a large extent. AÂ particular variant has been identified as a majorÂ hetrozygous component which amounts as a major component for the breast cancer. The rigorous working on Human Genome projectÂ has proved thatÂ the family history plays a major role in detecting Breast cancer and also helps in gaining knowledge aboutÂ genetic variations which depicts as a high risk factor among all the cancer types. The overall observation has concluded that the risk of this disease is mostly among the women community who has a family history. The ultimate aim is to classify the genes that are most significant and non-significant among all the genes present in the breast cancer tissue at the early stages usingÂ Â Â NaÃ¯veâ€™s Bayesianâ€™s and c5.0 algorithm and hence build a predictorÂ modelÂ toÂ Â predict breast cancer using ANNâ€™s Kernal based method.Â